Estimasi Ketebalan Sedimen dan Kedalaman Diskontinuitas Mohorovicic Daerah Jawa Timur dengan Analisis Power Spectrum Data Anomlai Gravitasi - Dwi Indriana, Rina (BERKALA FISIKA, 2008)
Gravitation anomaly research had been done to predict the depth of sediment. The gravitation research covered East Java from north coast to south coast, Indonesia. By using power spectrum method the average of sediment depth could predicted. Power spectrum method based on FFT theorem. A Short wavelength signal was correspond to narrow source and a long waveleght signal corresponds with shallow source. The power spectrum result was two discontinuities. The depth of narrow discontinuity is 2,7 km and 25,6 for the shallow continuity. The shallow discontinuity predicted as Mohorovicic layer.Â Keyword: power spectrum, gravitation anomaly, discontinuity